2021
DOI: 10.3390/met11040637
|View full text |Cite|
|
Sign up to set email alerts
|

Review and Assessment of the Effect of Hydrogen Gas Pressure on the Embrittlement of Steels in Gaseous Hydrogen Environment

Abstract: Hydrogen gas pressure is an important test parameter when considering materials for high-pressure hydrogen applications. A large set of data on the effect of hydrogen gas pressure on mechanical properties in gaseous hydrogen experiments was reviewed. The data were analyzed by converting pressures into fugacities (f) and by fitting the data using an f|n| power law. For 95% of the data sets, |n| was smaller than 0.37, which was discussed in the context of (i) rate-limiting steps in the hydrogen reaction chain an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…Using this set of equations requires both b HH and b Gas for the calculation of f HH in a gas mixture according Equation (2). Within the given temperature and pressure range for most engineering applications, the co-volume constant of hydrogen can be assumed as constant (b HH = 15.84 cm 3 /mol [10]) whereas the co-volume constant of the other gas (b Gas ) can be derived from Equation (4) as a function of pressure using experimentally measured compressibility factors.…”
Section: Fugacity Of Hydrogen In Gas Mixturesmentioning
confidence: 99%
See 2 more Smart Citations
“…Using this set of equations requires both b HH and b Gas for the calculation of f HH in a gas mixture according Equation (2). Within the given temperature and pressure range for most engineering applications, the co-volume constant of hydrogen can be assumed as constant (b HH = 15.84 cm 3 /mol [10]) whereas the co-volume constant of the other gas (b Gas ) can be derived from Equation (4) as a function of pressure using experimentally measured compressibility factors.…”
Section: Fugacity Of Hydrogen In Gas Mixturesmentioning
confidence: 99%
“…Using the data from Figure 2, the co-volume constant of the respective gas mixture b (N 2 -H 2 or CH 4 -H 2 ) can be calculated according to Equation (5), and finally the fugacity of hydrogen in a gas mixture f HH can be calculated according to Equation (2).…”
Section: Fugacity Of Hydrogen In Gas Mixturesmentioning
confidence: 99%
See 1 more Smart Citation
“…More and more attention has been paid to the safety of transportation equipment [1][2][3]. Facing the energy crisis, hydrogen-fueled vehicles are recognized as a most promising solution [4][5][6][7]. Compared with electric vehicles, when refueling with energy, the hydrogen vehicle has advantages of technical simplicity and high filling rates [8].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that hydrogen embrittlement (HE) has become a serious problem since high-strength steel became widely used [5,7,13,14]. With the widespread application of aluminum alloys, it's found that aluminum and its alloys also have a higher hydrogen content [15][16][17].…”
Section: Introductionmentioning
confidence: 99%